Effects of filtration volume using powdered activated charcoal on the recovery of L (+)-lactic acid from sago starch - Bujang, Kopli; Ang, Shin Ying; Awang Adeni, Dayang Salwani (2006)
In this preliminary study, fine powdered activated charcoal (PAC) was used to recover lactic acid from the impurities existed in fermentation broth with different volume size of crude lactic acid. 200 g of activated charcoal in 1N hydrochloric acid (HCl) was packed into glass columns (49mm in diameter), followed by deionized water until pH around 6. Next, 0.5 L (or 2.5 mL/g PAC) and 1.0 L (or 5.0 mL/g PAC) of autoclaved cell-free fermentation broth was added to the glass columns, followed by 0.5 L and 1.0 L of deionized water respectively. It is observed that the efficiency of UV light absorbing compounds removal at ?200 and ?260 (%) is 94.42, 97.61 and 92.55, 97.56 respectively for 0.5L and 1.0L of fermentation broth. Color removal efficiency is observed to be the same (more than 99%) whereas lactic acid recovery increases from 13.56% to 46.43% with the ascend of sample (fermentation broth) volume loaded. On the other hand, the recovery of lactic acid by deionized water (0.5 and 1.0L) is 84.04% and 51.86% respectively. It gives a total recovery of 97.60 and 98.29% respectively for both parameters. Protein and glucose recove